2016
DOI: 10.3906/bot-1512-13
|View full text |Cite
|
Sign up to set email alerts
|

In vitro seed germination, plantlet growth, tuberization, and syntheticseed production of Serapias vomeracea (Burm.f.) Briq.

Abstract: Orchids are considered recalcitrant plants in in vitro propagation. Due to the lack of appropriate micropropagation techniques for mass production and damage to their ecological distribution posed by local gatherers, these species are threatened with extinction, including Serapias vomeracea (Burm.f.) Briq. In this research, we put forward a complete micropropagation method covering in vitro micropropagation, synthetic seed formation, germination in soil, and acclimatization to ambient conditions. To the best o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In the current study, zeatin was more effective than BAP for microrhizome induction of Bentong ginger. It is in agreement with the previous report that zeatin was more effective for the in vitro tuber formation of Serapias vomeracea than BAP, kinetin, thidiazuron (TDZ) and 2-isopentenyl adenine (2-iP) [36]. It stated that cytokinin enrichment in the storage organ formation zone stimulates storage organ initiation and favors the growth of young storage organs by stimulating cell division during the early stages of growth, but they do not regulate further phases of storage organ growth [23].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, zeatin was more effective than BAP for microrhizome induction of Bentong ginger. It is in agreement with the previous report that zeatin was more effective for the in vitro tuber formation of Serapias vomeracea than BAP, kinetin, thidiazuron (TDZ) and 2-isopentenyl adenine (2-iP) [36]. It stated that cytokinin enrichment in the storage organ formation zone stimulates storage organ initiation and favors the growth of young storage organs by stimulating cell division during the early stages of growth, but they do not regulate further phases of storage organ growth [23].…”
Section: Discussionsupporting
confidence: 93%
“…incarnata , the highest shoot and root growth rate was observed on the medium containing 2iP [35]. Bektas et al, [3] have also reported, both BA and 2iP highly favored shoot formation of protocorms in Orchis coriophora .…”
Section: Resultsmentioning
confidence: 99%
“…Seed viability was found to be 54±2.1%. However, in a similar study on S. vomeracea, the result of seed viability was not indicated (22). Plant seeds need a carbon and energy source until they germinate and become autotrophic when cultured in (23).…”
Section: Discussionmentioning
confidence: 95%